2015
DOI: 10.1177/0363546515611652
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Reference Points Are Inaccurate With and Without a True Lateral Radiograph

Abstract: Background: Studies have reported methods for radiographically delineating medial patellofemoral ligament (MPFL) femoral tunnel position on a true lateral knee radiograph. However, obtaining a true lateral fluoroscopic radiograph intraoperatively can be challenging, rendering radiographic methods for tunnel positioning potentially inaccurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 50 publications
4
52
0
1
Order By: Relevance
“…Our findings validate previous results. 10 Moreover, our study is in agreement with that of Ziegler et al, 19 who demonstrated that even using a pure lateral radiological view as recommended by Schöttle et al, 12 the radiological method is not a precise method to determine the anatomic femoral fixation point of the MPFL. In our study, we also used a strict lateral view.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings validate previous results. 10 Moreover, our study is in agreement with that of Ziegler et al, 19 who demonstrated that even using a pure lateral radiological view as recommended by Schöttle et al, 12 the radiological method is not a precise method to determine the anatomic femoral fixation point of the MPFL. In our study, we also used a strict lateral view.…”
Section: Discussionsupporting
confidence: 91%
“…In this ideal situation, the authors found a mean distance of 4.1 mm from the anatomic MPFL attachment. 19 If the lateral radiograph is not strictly lateral, the error is even greater. Just a small 5° rotation will have a significant effect in determining the anatomic femoral fixation point (7.5-9.2 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of lateral radiographs may also be considered a limitation of this study, especially given recent criticism of the use of radiologic measures due to their inherent risk of error. 50 Although 3-dimensional imaging may provide a more accurate measure of the exact location of the femoral tunnel, this was not a feasible test on this large clinical cohort, and valid and reliable measurement methods have not been reported. The low number of poor tunnels assessed in the cohort may influence the statistical power of this group’s correlation to the BPII.…”
Section: Discussionmentioning
confidence: 95%
“…Ziegler et al [ 26 ] emphasised the importance of a true lateral radiograph using normal cadaveric knees. The position of the MPFL tunnel was 4 mm away from the true MPFL origin as defined by dissection, worsened by even 2.5° rotation of the image.…”
Section: Discussionmentioning
confidence: 99%